MINIMIZING RENOVATION PROJECT DELAYS (Case Study: Fuel Station A) - Soraya Khaerunnisa; Akbar Adhiutama (SEAN Institute, 2023)
PT XYZ is a PT ABC (Persero) subsidiary under Sub-Holding Commercial & Trading, PT KLM. PT XYZ is responsible for operating COCO gas stations owned by PT ABC. As time goes by, PT ABC's competitors are increasingly developing their business and increasing their outlets, which will become a challenge for PT XYZ. As one of the efforts to deal with this competition, PT XYZ is constantly upgrading and improving the appearance of gas station facilities, ensuring that the facilities function correctly so that customers will feel comfortable and always fill their vehicles at COCO gas stations. This is also stated in the company's strategy and listed in the 5R program (Ringkas (Brief), Rapi (Neat), Resik (Clean), Rawat (Caring), Rajin (Diligent)). To accommodate the above strategy, PT XYZ also allocates a capital goods investment to implement repairs/renovations in the existing Fuel Station. In practice, the project’s physical performance gap caused PT XYZ to not achieve the Key Performance Indicator according to the target. The Technical function as the executor function in the implementation of the projects plays a vital role in implementing the project on time, which will undoubtedly affect the project’s performance in PT XYZ. The Key Performance Indicator also cascaded to Technical Function as the Construction Accuracy Performance point. The purpose of this study is to find the root causes of the obstacles faced by PT XYZ in project planning and find solutions to solve these problems so that the project can be completed on time and the KPI for Non-Business Development Capital Goods Investment is achieved. To look for problems, research was conducted at a gas station in the Jabodetabek area with specific criteria. Interview methods will be conducted with stakeholders who play a role in the gas station renovation project. The current reality tree method will analyze problem identification to get the root cause. Case studies and literature reviews will be conducted to find a theory to resolve the root cause. PMBOK, especially in the project schedule management and planning process group sections, and Operation Management theory, especially Lean Production, will be used to analyze the project's performance and find a solution. Several alternative solutions will be identified based on the root cause obtained. Then the best alternative solutions will be selected by using AHP (Analytical Hierarchy Process) with the criteria and rating of the results of interviews with stakeholders. An implementation plan for the best alternative solution will be designed and used as a recommendation for the company.